A Context-Aware Framework to Manage the Priority of Injured Persons Arriving at Emergencies - Ouakasse, Fathia; Stitini, Oumaima; Rakrak, Said (International Journal of Online and Biomedical Engineering (iJOE), 2023)
The integration of Internet of Medical Things (IoMT) in Hospital system has modified the traditional medical service as a reactive system based on hospitalization and diseases to a preventive and interoperable system based mainly on the interactive data flow between patient and health professionals. Using medical connected objects (MCOs), medical data is collected and processed. According to gathered data, the new medical system should be able to sort patient states based on urgent and critical vital signs, and consequently priorities are defined. In this paper, we direct our attention to manage priority in hospital emergencies in order to adapt dynamically operations and interactions with different stakeholders according to the changes in their execution context. Indeed, based on data sensed from MCOs implemented in ambulances, emergency rooms might be prepared to receive injured persons like victims of road accidents or other incidents. Therefore, we design a context-aware monitoring framework for injured people based on gathered medical data to manage priorities.